Change Management Perspectives in an ERP Module Implementation: A Case Study in a Telecommunication Company - Tota Simatupang; Rajesri Govindaraju; Reni Amaranti (Institute of Research and Community Outreach - Petra Christian University, 2016)
Successful Enterprise Resource Planning (ERP) projects require change management to support the integration of the ERP systems into work environment because ERP imple¬men¬tations involve lots of changes on technical infrastructures, business processes, organization structure, rules and skills of people in the organization. This study was aimed to explain the challenges in implementing an ERP module in a Indonesian telecommunication company, focusing on the change management process involves in the project. A case study at a tele¬com¬munication company was used to collect empirical data and to analyses important aspects of project arrangements that will have an impact on the change management process accompanying the ERP implementation project. The following two aspects of changes were analyzed as the impact of ERP implementation: changes in individual behaviors and changes in the organisational practices. Based on the empirical study, two important aspects of change management effectiveness in the project and post-project stage were highlighted: alignment of the organization structure to support IT-business collaboration and alignment of employee orientation towards effective use of ERP systems. Besides, this study also highlighted that it is important to plan and execute change management process in the post-project stage to obtain benefits from ERP implementation.